Kecerdasan dan Kinerja Karyawan - Siswanto, Siswanto; Ma’rufah, Fitri Setya (Fakultas Ekonomi, UIN Maliki Malang, 2019)
Intelligencies have an important role to improve employee performance. There was a Â research gap related to the role. This research is to analyze the effect of intelligence dimensions on employee performance. The sample of the study consisted of 67 respondents. Quantitative analysis is used. The results showed intellectual quotient, emotional quotient, and spiritual quotient could improve employee performance. Meanwhile, spiritual intelligence had a dominant role.